ENHANCING CRITICAL THINKING SKILLS OF STUDENTS IN ENGLISH CLASSES (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In the rapidly evolving world of higher education, developing critical thinking skills among students is worthy of attention. This article explores effective strategies for enhancing critical thinking in English classes, particularly in a higher education context. By integrating specific pedagogical methods, English instructors can significantly contribute to the intellectual growth of their students. The discussion encompasses various research-backed methods, practical classroom activities, and the overarching benefits of nurturing critical thinking skills.